The spin-1/2 Heisenberg ferromagnet on the pyrochlore lattice: A Green's function study - Hutak, T.; Müller, P; Richter, J.; Krokhmalskii, T.; Derzhko, O. (Condensed Matter Physics, 2018)
We consider the pyrochlore-lattice quantum Heisenberg ferromagnet and discuss the properties of this spin model at arbitrary temperatures. To this end, we use the Green’s function technique within the random-phase (or Tyablikov) approximation as well as the linear spin-wave theory and quantum Monte Carlo simulations. We compare our results to the ones obtained recently by other methods to corroborate our findings. Finally, we contrast our results with the ones for the simple-cubic-lattice case: both lattices are identical at the mean-field level. We demonstrate that thermal fluctuations are more efficient in the pyrochlore case (finite-temperature frustration effects). Our results may be of use for interpreting experimental data for ferromagnetic pyrochlore materials. Ми розглядаємо квантовий феромагнетик Гайзенберга на гратцi пiрохлору i обговорюємо властивостi цiєї спiнової моделi при довiльних температурах. Для цього ми використовуємо технiку функцiй Грiна у наближеннi хаотичних фаз (наближеннi Тяблiкова), а також лiнiйну теорiю спiнових хвиль i симуляцiї методом квантового Монте Карло. Для пiдтвердження наших результатiв ми порiвнюємо їх з отриманими недавно iншими способами. Нарештi ми спiвставляємо нашi результати з вiдповiдними для простої кубiчної гратки, адже обидвi гратки iдентичнi у середньопольовiй картинi. Ми показуємо, що тепловi флуктуацiї ефективнiшi у випадку гратки пiрохлору (ефекти фрустрацiї при скiнченних температурах). Нашi результати можна використати для тлумачення експериментальних даних для матерiалiв, у яких реалiзується феромагнетик на гратцi пiрохлору.